Correction: Recent advances in microfluidic-based electroporation techniques for cell membranes. Issue 17 (2nd August 2022) - Wang, Fei; Lin, Shujing; Yu, Zixian; Wang, Yanpu; Zhang, Di; Cao, Chengxi; Wang, Zhigang; Cui, Daxiang; Chen, Di
Abstract : Correction for 'Recent advances in microfluidic-based electroporation techniques for cell membranes' by Fei Wang et al., Lab Chip, 2022, 22, 2624–2646, ; https://doi.org/10.1039/D2LC00122E .